2000
DOI: 10.1063/1.1288031
|View full text |Cite
|
Sign up to set email alerts
|

Rate equations for collision-induced desorption and abstraction in the reaction system H(g)+D/Si(100)→D2,HD at 573 K

Abstract: Abstraction and desorption kinetics in the reaction of H + D/Si (100) and the relation to surface structure Abstraction of chemisorbed bromine from the Si(111) surface by incident hydrogen atoms Collision-induced desorption ͑CID͒ and Eley-Rideal ͑ER͒ type abstraction have been investigated in the reaction system, H(g)ϩD ad /Si͑100͒→D 2 ,HD, at surface temperature of 573 K where dihydride phase is unstable. Rate equations for CID were obtained based on a second-order kinetics with respect to doubly occupied Si … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Besides, taking into account the feature that the ABS rate curve is a simply decreasing function with decreasing D on the saturated surface, the maximum in the HD rate around D ϭ0.85 ML is attributed to HD CID overlapping ABS. With the light of the present results and the rate-curve analysis done at T s ϭ573 K, 14 we confirm that Eq. ͑1͒ and the physics and chemistry behind it are valid.…”
Section: ͑1͒supporting
confidence: 86%
See 1 more Smart Citation
“…Besides, taking into account the feature that the ABS rate curve is a simply decreasing function with decreasing D on the saturated surface, the maximum in the HD rate around D ϭ0.85 ML is attributed to HD CID overlapping ABS. With the light of the present results and the rate-curve analysis done at T s ϭ573 K, 14 we confirm that Eq. ͑1͒ and the physics and chemistry behind it are valid.…”
Section: ͑1͒supporting
confidence: 86%
“…Actually, the observed HD rate curves exhibit a bimodal structure particularly at small initial D coverages D 0 , suggesting the occurrence of two distinct channels, i.e., HD CID along the LH mechanism and ABS via the direct ER mechanism. 7 Khanom et al 14 propose a HD rate equation to fit to the experimental data obtained for D 0 ϭ1.0 ML ͑ML: monolayer, one D atom per surface Si atom͒, dN HD dt ϭk ABS DD ϩC 1 HD DD ϩ2C 2 HD HD ϩC 3 HD HH ,…”
mentioning
confidence: 99%
“…This is because possible isotope effects are included in the ABS and AID processes when lighter atoms are preferentially abstracted in such a H and D coadsorption system. 18,43 Figure 5 shows the plots of the initial HD and D 2 rates measured as a function of T s . The measured AID rate curve for the D 2 desorption has a peak in the temperature region 470 K ഛ T s ഛ 600 K. The observed peak of the AID rate curve is much broader than the peak previously observed on the nonsaturated 1.0 ML D / Si ͑100͒ surface.…”
Section: A Experimental Abs and Aid Ratesmentioning
confidence: 99%
“…So far, the abstraction reactions have been studied mainly from a kinetics point of view [9][10][11][12][13][14][15][16][17][18][19][20][21][22] rather than from a dynamics point of view. [23][24][25][26][27] Dinger, Lutterloh, and Küppers 9,20 reported that the reactions of Eqs.…”
Section: Introductionmentioning
confidence: 99%
“…This hydrogen abstraction ͑ABS͒ by gas phase H atoms is of great technological relevance to electronic device processes such as plasma-enhanced chemical vapor deposition of thin Si films. 1 So far, the kinetic mechanism of the hydrogen abstraction reactions has been extensively studied by isotopic labeling of adatoms in the system HϩD/Si from an uptake [2][3][4][5][6][7][8][9] as well as from a desorption [10][11][12][13][14][15][16][17][18][19] point of view. It has been well established that the abstraction reactions observed in the desorption experiments 13,14,18,19 can be categorized either into a direct abstraction ͑ABS͒ of adatoms by gas phase atoms to form HD molecules, ABS: HϩD/Si→HD, or into an indirect abstraction or adsorption-induced desorption ͑AID͒ of surface adatoms to form D 2 molecules, AID: HϩD/Si→D 2 .…”
Section: Introductionmentioning
confidence: 99%